HUBUNGAN SARAPAN PAGI DENGAN TINGKAT KONSENTRASI BELAJAR PADA ANAK KELAS 4-6 SEKOLAH DASAR NEGERI 1 TIYINGGADING - Desak Gede Yenny Apriani (JURNAL MEDIKA USADA, 2022)
Background: Children who regularly eat breakfast have enough energy to receive lessons at school than children who skip breakfast. Children who skip breakfast often show weakness, dizziness or fainting. These things really do not support the learning process because learning concentration is disturbed. In learning activities, concentration plays an important role in achieving a conducive learning atmosphere because it reflects children's cognitive abilities. Purpose: This study aims to determine the relationship between breakfast and the level of learning concentration in grade 4-6 at Tiyinggading 1 Public Elementary School. Method: This research is a descriptive analytic study with a cross sectional approach. The sampling technique is Total Sampling. The research subjects were 41 students of grade 4-6 at Tiyinggading 1 Public Elementary School. The independent variable includes breakfast habits and the dependent variable is the level of concentration. Data were analyzed using the Chi-Square test. Result: The average percentage of breakfast for children in grades 4-6 at Tiyinggading 1 State Elementary School is 34 people, 83%. The category of learning concentration for children in grades 4-6 at SD Negeri 1 Tiyinggading has a good average, namely 31 people 76% and there is a significant relationship between breakfast and the level of learning concentration with a value of p = 0.001. Conclusion: Based on the results of the study, it can be concluded that breakfast is related to the level of learning concentration, therefore parents are expected to provide their children with breakfast in order to increase brain performance where breakfast has benefits in providing energy to the brain so that it can help improve memory, reduce the risk of anemia. and concentration while studying. Key words: Breakfast, study concentration, pre-school.